The appeal of beauty and physical attractiveness: An Indian perspective - MADAN, Shilpa (Institutional Knowledge at Singapore Management University, 2017)
Marketing to India’s diverse and rapidly changing consumers requires constant refreshment of knowledge and skills. To the keen MBA student specializing in marketing as well as its ardent practitioner, this book blends practical insights with theoretical frameworks.